Pengaruh Design Thinking Model Berbantuan Genially Terhadap Kemampuan Pemecahan Masalah dan Kolaboratif Siswa Sekolah Dasar - Dwiyanti, Fery; Yanuarto, Wanda Nugroho (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study examined the effect of the Design Thinking Model assisted by Genially on elementary school students' problem-solving and collaborative skills and analyzed the relationship between the two skills. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The study involved fourth-grade students in the Sutomo Cluster, Cilacap Tengah District, consisting of an experimental class that learned through the Design Thinking Model assisted by Genially and a control class that learned through the Design Thinking Model supported by conventional media. Data were collected using a problem-solving test, collaborative skill questionnaire, observation sheet, and documentation. The instruments were validated by experts and tested for reliability before use. Data were analyzed through normality and homogeneity tests, independent sample t-test, simple linear regression, and Pearson correlation. The findings showed that the experimental class obtained higher posttest scores in problem-solving skills (M = 89.48) than the control class (M = 71.03). The experimental class also obtained higher collaborative skill scores (M = 86.61) than the control class (M = 40.10). These results indicate that the integration of Design Thinking and Genially provides a structured, visual, and interactive learning experience that strengthens students' ability to identify problems, develop ideas, test solutions, communicate, and work in groups. This study contributes to elementary IPAS learning by offering an instructional model that simultaneously develops cognitive and social skills. Further studies are recommended to involve broader samples and longer intervention periods.